Vampire diaries : The Return : Shadow Souls / [book 6] - Smith, L. J., 1965- (Lisa Jane) (London : Hodder Children's Books, 2010)
Elena must come to terms with her altered physical state. Even she can barely comprehend what she is now capable of. Finding herself forced to travel to the Dark Dimension with Damon, Elena is secretly terrified of letting her long-disguised feelings for Damon run wild. For if Damon does lure her into becoming his dark princess, her new power might not be used for good...
Keywords: fantasy romány -- upírske príbehy -- tajomné romány -- ľúbostné romány -- americká literatúra -- knihy v anglickom jazyku; americké romány; Young Adult; cudzojazyčná literatúra